Implementação de um sistema de documentação para o estudo técnico de pinturas académicas de Adriano de Sousa Lopes na Faculdade de Belas-Artes da Universidade de Lisboa (FBAUL) - Cardeira, L (2018)
The present article intends to present a model for the documentation and registry used in the diagnosis and intervention stages in conservation and restoration (C&R) of a set of twelve works by Adriano de Sousa Lopes, from the collection of the Faculty of Fine Arts, University of Lisbon (FBAUL). To this end, a free and open access geographic information system (GIS) software called QGIS® was used. During the analysis, several vector maps were produced, both for diagnosis and for conservation and restoration treatments (CR), namely the microcracks network, areas of loss, consolidation areas, textile microsurgery and chemical cleaning. The quantitative results obtained from the spatial analyses of the pictorial surfaces were recorded in the GIS database. Finally, it was verified that the technical study of works with the QGIS(R) program contemplates a spatial perception of the works of art for evidencing, in a systematic and integrated way, the phenomena of alteration of the pieces under analysis.